Peran Arisan Sapi dalam Meningkatkan Kesejahteraan Masyarakat di Desa Air Hitam Laut Kecamatan Sadu - Muhammad Tang; Daud Daud; Siti Fatimah; Haeran Haeran; Erwina Kartika Devi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the mechanism of the implementation of cattle arisan and analyze its role in improving the economic welfare of the community in Air Hitam Laut Village. Cattle arisan is a form of local wisdom based on mutual cooperation carried out by the community as an alternative to fulfilling the needs of sacrificial animals and a means of long-term collective investment. This activity not only has social and spiritual value, but also has a significant economic impact on participants. This study uses a descriptive qualitative approach. Data collection techniques are carried out through observation, in-depth interviews with arisan participants, community leaders, and religious leaders, as well as documentation from the cattle arisan group. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of cattle arisan begins with the formation of small groups in the hamlet or RT environment. Group members agree on routine monthly contributions collected to buy one cow every month. In the perspective of Islamic economics, cattle arisan is a form of ta'awun (mutual assistance) that is in accordance with sharia principles, free from usury, gharar, and maysir, and reflects justice and the spirit of empowering the people's economy.